2005
DOI: 10.1002/gcc.20217
|View full text |Cite
|
Sign up to set email alerts
|

Complex chromosome aberrations persist in individuals many years after occupational exposure to densely ionizing radiation: An mFISH study

Abstract: Long-lived, sensitive, and specific biomarkers of particular mutagenic agents are much sought after and potentially have broad applications in the fields of cancer biology, epidemiology, and prevention. Many clastogens induce a spectrum of chromosome aberrations, and some of them can be exploited as biomarkers of exposure. Densely ionizing radiation, for example, alpha particle radiation (from radon or plutonium) and neutron radiation, preferentially induces complex chromosome aberrations, which can be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 55 publications
5
35
0
Order By: Relevance
“…Clearly this peripheral blood lymphocyte has not been through many, if any, cell divisions and was perhaps irradiated directly, not as a result of plutonium in the bone marrow, but as it passed by plutonium deposited in the lymph nodes. Therefore, three of the four plutonium workers exhibited cells with multiple chromosome rearrangements, supporting suggestions that their presence can be used as indicative of exposure to aparticle radiation (Anderson et al 2000(Anderson et al , 2005Barquinero et al 2004;Hande et al 2005;Curwen et al 2012). Dicentrics were observed in three of the five men with external exposure and two of the plutonium workers (Table 3).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Clearly this peripheral blood lymphocyte has not been through many, if any, cell divisions and was perhaps irradiated directly, not as a result of plutonium in the bone marrow, but as it passed by plutonium deposited in the lymph nodes. Therefore, three of the four plutonium workers exhibited cells with multiple chromosome rearrangements, supporting suggestions that their presence can be used as indicative of exposure to aparticle radiation (Anderson et al 2000(Anderson et al , 2005Barquinero et al 2004;Hande et al 2005;Curwen et al 2012). Dicentrics were observed in three of the five men with external exposure and two of the plutonium workers (Table 3).…”
Section: Discussionsupporting
confidence: 54%
“…Support for this comes from the in vitro work on long-term cultures reported here. Nevertheless, stable cells containing multiple aberrations are induced by a-particle radiation, albeit in small numbers, and have been observed in studies of workers exposed to internally deposited plutonium (Tawn et al 1985;Whitehouse et al 1998;Anderson et al 2005;Hande et al 2005;Livingston et al 2006;Tawn et al 2006;Sotnik et al 2014). In the current study, such cells were found in three of the nine men (Table 3).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the mFISH technique, all 21 chromosomes (1-19, X and Y) are each painted in a different color, using combinatorial labeling, so that any interchromosomal translocations are observed as color junctions on individual chromosomes. The experimental procedure is outlined in earlier publications (Greulich et al, 2000;Hande et al, 2003;Hande et al, 2005).…”
Section: Cytokinesis-blocked Micronucleus Analysis (Cbmn)mentioning
confidence: 99%
“…Copyright © 2012 S. Karger AG, Basel Of the different kinds of genetic damage used as markers for past exposure to chromosome breaking agents, socalled clastogens, some are stable and can therefore be detected even decades after exposure, whereas others are unstable and lose their detectability within a few years. To the first category belong chromosomal translocations which are either assessed with the help of chromosome banding [Awa, 1997] or after fluorescent in situ hybridization (FISH), also referred to as 'chromosome painting' [Lucas, 1997;Hande et al, 2005]. Translocations have, for instance, been found in the lymphocytes of atomic bomb survivors of Hiroshima and Nagasaki, and it has been shown that their frequency does not substantially change with time [Kodama et al, 2001].…”
mentioning
confidence: 99%